A Review of Phytochemistry and Antimicrobial Properties of Essential Oil from Coriander (Coriandrum sativum L., Apiaceae) - Antônia Nádia Brito dos Santos; Francisca Lidiane Linhares de Aguiar; Andréa Maria Neves; Raquel Oliveira dos Santos Fontenelle (Archives of Current Research International, 2025)
Aim: The study is a systematic review of the literature with emphasis on the chemical and antimicrobial properties of Coriandrum sativum essential oil. Popularly known as coriander, the annual plant is an edible herb and cultivated all over the world, the plant-based compounds have been one of the alternatives in therapeutic and infectious disease treatments. Methodology: An electronic search was performed using the PubMed/MEDLINE (Medical Literature Analysis and Retrieval System Online), Scopus and Web of Science databases. Articles were selected within the range from January 2014 to September 2024, which were within the theme of antibacterial, antifungal and phytochemical profile. Results: Interesting results showed that the essential oil of C. sativum has an important antimicrobial activity against a range of microorganisms, including Gram-negative and Gram-positive bacteria, yeasts and filamentous fungi of clinical importance, proving to be a biological product with potential for the pharmaceutical industry in the advancement of new antifungals and the control of microbial resistance. The fruits and seeds of C. sativum have a similar chemical composition, predominantly comprising oxygenated monoterpenes, whereas the leaves contain saturated fatty aldehydes and alcohols as major compounds. Conclusion: In conclusion, the essential oils of various parts of C. sativum, as well as their constituents, can be considered as treatments for infectious diseases caused by bacteria and fungi of great clinical importance. However, further studies should explore the mechanisms of activity and cytotoxic effects.